Natural Law and Goodness in Thomistic Ethics. Issue 1 (8th February 2017) - Coyle, Sean
Abstract : The purpose of the essay is to recover a correct conception of natural law and goodness in the ethics of Saint Thomas Aquinas. It suggests that the dominant interpretation of Thomism known by legal philosophers—that of John Finnis—is importantly at variance with Aquinas's true account. Against the dominant interpretation, a true account of natural law must (i) differentiate between natural law and ethics in the full sense (moral theology), and (ii) interpret references to human good as references to virtuous goodness rather than non-moral goodness. The main body of the essay explores the place of these concepts in Aquinas's account of ethics.